Mapping women's empowerment : experiences from Bangladesh, India, and Pakistan - Azim, Firdous, 1952-; Sultan, Maheen (University Press Limited, 2010)
Papers presented at the Scoping Workshop of the South Asia Hub of the Women's Empowerment Programme sponsored by BRAC University, held from August 18-21, 2006 in Dhaka.